Mathematical modelling approach to understanding the effect of Mg-rich synthetic gypsum used as fertilizer on growth of Hevea brasiliensis in acid soils. - Fatai Arolu Ayanda; Mohd Firdaus Mohd Anuar; Susilawati Kashim; Oladosu Yusuff; Ibrahim Wasiu Arolu; Olabisi Fatimo Adekola; Adrian Crew (PLoS ONE)
Knowledge of plant growth dynamics is essential where constraints such as COVID-19 lockdown restrictions have limited its field establishment. Thus, modeling can be used to predict plant performance where field planting/monitoring cannot be achieved. This study was conducted on the growth dynamics of rubber planted on two acid soils treated with either dolomitic limestone (GML), kieserite or Mg-rich synthetic gypsum (MRSG) to supply the Mg required by rubber seedlings. To understand the effect of applied treatments on the changes in rubber growth, data on plant height, stem diameter and biomass were regressed against months after transplanting (MAT) using the equation y = A/ (1+be-ct), and its derivative [Formula: see text] was utilized for estimating the growth rate of the parameters. The dynamics in plant height, stem girth and plant biomass were modelled using an exponential function of y = Aebt and their rate of change was derived using dx/dy = Abebt. The experiment indicated that the logistic growth curve model expressed as y = A/ (1+be-ct), closely described the growth in terms of each parameter against months after transplanting. A high probability level (a = 0.0001) was recorded in the model for all the treatments in the study. The growth of rubber seedlings in the glasshouse was improved by MRSG treatment in the two studied soils (Ultisol and Oxisol), giving comparable results to other Mg fertilizer treatments. The plant performed better on the Ultisol compared to the Oxisol. The results indicate the potential of using MRSG to replace conventional Mg-fertilizers to sustain rubber seedling growth.